Phenomenological Study of Punk Community Hijrah at the Laskar Berani Hijrah Foundation in Depok - Dano, Muhammad Yanuar; Ronda, Andi Mirza (Eastasouth Institute, 2025)
This study aims to further explore the Punk Hijrah community under the auspices of the Laskar Berani Hijrah Foundation, focusing on understanding the meaning of hijrah among its members. The study questions whether hijrah is understood merely as a change in appearance like a Muslim, or if there is a deeper meaning related to changes in behavior and values. Jean Baudrillard's concept of Simulacra, which posits that modern humans often use things based on symbols rather than function and need, serves as a theoretical basis for this research. The research employs a qualitative method with Alfred Schutz's phenomenological approach, emphasizing the construction of meaning. Meaning construction is understood as the process of producing meaning through language, which is always dynamic and open to new interpretations and perspectives. For analysis, the Social Construction of Reality Theory is used as a guide to reveal the meaning of hijrah, the values of hijrah, the motives for hijrah, and the experiences of individuals who have experienced hijrah in the community. Specifically, this study analyzes the perspectives of punk community members who have joined the Laskar Berani Hijrah Foundation in Depok, aiming to uncover how the foundation's culture influences the hijrah desires of these punk youth. Through this research, it is hoped that the meaning of hijrah as understood by foundation members can be discovered, as well as how these values are internalized in their daily lives.